Ferroptosis-immune-metabolic axis in asthma: mechanistic crosstalk, endotype-specific regulation, and translational targeting - Ni, Feng-Xian; Hu, Jie; Chen, Pei-Sheng; Chen, Hui-Hui; Huang, Dong-Hui; Jiang, Ze-Bo (Frontiers in Immunology, 2026)
Asthma, a heterogeneous chronic respiratory disorder affecting millions globally, is driven by complex interactions between genetic susceptibility, environmental triggers, and dysregulated immunity. Emerging evidence positions ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, as a pivotal mechanism. This review introduces the “Ferroptosis-Immune-Metabolic Axis” as an integrative framework for asthma pathogenesis. We detail how environmental insults (e.g., allergens, pollutants) initiate ferroptosis in airway epithelial cells, leading to the release of damage-associated molecular patterns (DAMPs) and lipid peroxidation products (e.g., 4-HNE). These molecules activate and recruit immune cells (M1 macrophages, neutrophils, Th17 cells), which in turn exacerbate oxidative stress and iron dysregulation, creating a self-amplifying cycle. Metabolic reprogramming, including enhanced polyunsaturated fatty acid (PUFA) synthesis and glycolytic flux, provides the essential substrates and energy to sustain this vicious cycle. We dissect endotype-specific manifestations: IL-33-driven epithelial ferroptosis in eosinophilic asthma and ALOX15-mediated lipid peroxidation coupled with hepcidin-induced iron retention in neutrophilic asthma. Therapeutically, we highlight novel strategies such as inhaled GPX4 mRNA nanocarriers and ALOX15 inhibitors, underscoring the potential of targeting this axis for precision medicine in refractory asthma.